CX3CR1 fate mapping in vivo distinguishes cochlear resident and recruited macrophages after acoustic trauma - Murali, Sree Varshini; Stothert, Andrew R.; Pereyra, Elyssa; Batalkina, Lyudmila; Kaur, Tejbeer (Frontiers in Immunology, 2025)
IntroductionCochlear injury activates the resident macrophages (RM) and recruits the blood-circulating monocytes and monocyte-derived macrophages (Mo/Mo-M), but their specific functions in the injured cochlea are unknown. It is well-established that the chemokine fractalkine receptor (CX3CR1), expressed by cochlear macrophages, influences the density of those macrophages and promotes synaptic repair and spiral ganglion neuron (SGN) survival in the injured cochlea. As CX3CR1 is expressed on both RM and Mo/Mo-M, it remains unclear if CX3CR1- expressing RM and Mo/Mo-M are distinct and differentially promote SGN survival after cochlear injury.MethodsWe used a fate mapping tamoxifen-inducible CX3CR1 mouse model (CX3CR1YFP−CreERT2/wildtype:R26RFP) wherein CX3CR1-expressing RM and Mo/Mo-M are endogenously labeled with different fluorescent reporters. Tamoxifen injections were performed intraperitoneally at 4 weeks of age, and recombination efficiency was evaluated after 2 and 60 days. Mice were subjected to an acoustic trauma of 112 decibel (dB) sound pressure level (SPL) at 8–16-kHz octave band, for 2 hours. Heterogeneity in cochlear macrophages was defined with respect to their origin, turnover, spatiotemporal distribution, morphology, and fate following acoustic trauma.ResultsAfter 60 days of tamoxifen injections at 4 weeks of age, long-lived cochlear RM were YFP+ RFP+ with 98.0% ± 1.7% recombinant efficiency, and short-lived blood-circulating CX3CR1 lineage (Mo/Mo-M) cells were YFP+ RFP− with 2.5% ± 1.1% recombinant efficiency. Following an acoustic trauma, morphologically similar RM and Mo/Mo-M were observed in the spiral ganglion, lamina, and ligament and around the sensory epithelium. The quantification of RM and Mo/Mo-M in the spiral lamina and ganglion revealed distinct spatial and temporal distribution patterns. Furthermore, recruited Mo/Mo-M expressed classical monocyte markers such as Ly6C and CCR2. Both RM and Mo/Mo-M were positive for proliferation marker, Ki67, and negative for apoptotic marker, cleaved caspase-3, suggesting that the overall increase in macrophage numbers in the noise-injured cochlea is a contribution of both the proliferation of RM and the recruitment of Mo/Mo-M. Probing for blood-clotting protein, fibrinogen, showed its presence in the cochlea after acoustic trauma, suggesting vascular damage that positively and strongly correlated with the time course of the recruitment of blood-circulating Mo/Mo-M in the noise-injured cochlea.DiscussionThese data imply that macrophages in the noise-injured cochlea are heterogeneous regarding their ontogeny, distribution, and fate. They offer a robust tool to study the precise roles of resident and recruited macrophages in healthy and pathological ears.